Gender differences in problematic gaming among Chinese adolescents and young adults - Zhenjiang Liao; Juan Le; Xinxin Chen; Ying Tang; Hongxian Shen; Qiuping Huang (BMC Psychiatry)
Abstract Background This study aimed to evaluate the prevalence of problematic gaming among Chinese adolescents and young adults (CAYAs) and identify potential gender-specific risk variables. Methods 6,014 CAYAs were selected for this cross-sectional study using online convenience sampling. To evaluate their sociodemographic qualities, gaming practices, problematic gaming (as measured by the Video Game Dependency Scale), gaming motivations, and personality traits (as measured by the Chinese Big Five Personality Inventory abbreviated version), participants filled out a self-report questionnaire. To identify the common and distinct variables associated with problematic gaming, stepwise logistic regression analyses were conducted independently for males and females. Results The study comprised 5,593 CAYAs in all (3326 males and 2267 females). Males were more likely than females to have problematic gaming (21.5% vs. 14.1%, p < 0.001). Problematic gaming among male and female CAYAs was substantially correlated with gaming patterns (monthly spending, daily time), gaming motivations (escaping reality, sensation seeking), and personality traits (conscientiousness, neuroticism). Additionally, among male CAYAs, problematic gaming was linked to the family structure of being an only child (OR: 0.715, 95%CI: 0.588–0.869, p = 0.001), lower than undergraduate (OR: 0.735, 95%CI: 0.603–0.896, P = 0.002), and the gaming motivation for coping with negative emotion ((N vs. Y, OR: 0.794, 95%CI: 0.653–0.965, p = 0.021). Problematic gaming was independently linked to the BRS gaming genre among female CAYAs (OR: 4.989, 95%CI: 2.728–9.125, p < 0.001). Female CAYAs with problematic gaming exhibit distinct characteristics. Conclusions Compared to female CAYAs, problematic gaming is much more common among male CAYAs. Cross-gender risks in gaming include extended playtime, excessive spending, high neuroticism, and low conscientiousness. Highly educated singles are at higher risk of problematic gaming. Playing BRS games was a specific risk factor for females. This study revealed significant gender disparities in the prevalence and risk factors of problematic gaming among CAYAs, underscoring the significance of gender-specific screening and interventions for CAYAs to prevent problematic gaming and its negative effects. Clinical trial number Not applicable.